African small publishers' catalogue 2021 - Higgs, Colleen, 1962-; Higgs, Colleen, 1962-; Smith, Aimee-Claire (Modjaji Books, 2021)
An invaluable reference book for publishers or anyone interested or in any way involved in the African book/publishing/literary scene, or writers looking for a publisher. Lists a wide range of over 60 small and independent publishers in countries from around Africa. The catalogue also contains articles about publishing the indie way, book-making in the time of COVID-19, and more. Includes publishers from South Africa, Ghana, Zimbabwe, Senegal, France, the United Kingdom, Switzerland, Nigeria, the United States, Canada, Togo, Mozambique, Morocco, Uganda, Rwanda, Malawi, Algeria, Egypt, Uganda, and Namibia.